NEW UZBEKISTAN - NEW NOTARIAT (American Journal of Research in Humanities and Social Sciences, 2024)
The article deals with the issues of reforming the legislation on notariat, creating conditions for more active participation of notary in the execution of notarial acts. And also, improvements of notariat in the strategy of actions on five priority directions of development of the Republic of Uzbekistan in 2017-2021.